Cerebellar ataxia in the elderly. - Safe, A F (1992)
In a retrospective study of 624 elderly patients referred with falls and gait disorders, 45 patients were found to have ataxia. Cerebrovascular diseases were the most common underlying cause of ataxia (15 patients, 37%). Nine patients had hereditary/degenerative cerebellar ataxia. History suggesting alcohol as an underlying cause was established in two patients with cerebellar ataxia. Three patients had normal pressure hydrocephalus and their condition improved remarkably after surgery. No definite cause was found in five patients. Cranial computed tomography (CT) showed cerebral atrophy in 16 patients and in three patients there was evidence of atrophy of the cerebellar vermis. Four patients had femoral neck fractures and three patients had other fractures. In a 5-year follow-up five patients died with bronchopneumonia (11% mortality) and patients with dementia showed rapid deterioration. All patients were referred to the day hospital for rehabilitation. The best treatment outcome was achieved in patients who had a single cerebrovascular accident with no cognitive impairment and in those whose ataxia was secondary to medication. Fourteen patients (44%) moved to residential care while 27 (66%) continued to live in their homes with community support. We concluded that there is no evidence of increased mortality in the elderly patients with cerebellar ataxia. CT scan is mainly helpful in diagnosing specific diseases such as tumours or hydrocephalus. A significant proportion of elderly patients with ataxia may have reversible or treatable conditions and can pursue an independent life.